2022
DOI: 10.1177/0272989x221118078
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Politically Motivated Reasoning

Abstract: Background During the COVID-19 pandemic, the world witnessed a partisan segregation of beliefs toward the global health crisis and its management. Politically motivated reasoning, the tendency to interpret information in accordance with individual motives to protect valued beliefs rather than objectively considering the facts, could represent a key process involved in the polarization of attitudes. The objective of this study was to explore politically motivated reasoning when participants assess information r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
3
4
0
Order By: Relevance
“…Again, potential interaction effects between statistical numeracy and cultural worldview variables were extensively investigated using multiple regression analyses and other modeling and extreme group approaches. All analyses again indicated that interaction effects were consistently unreliable in accordance with Study 1 and the growing literature documenting multiple failures to replicate previously reported evidence of polarization (Ballarini & Sloman, 2017; Maguire et al, 2022; Persson et al, 2021; Shoots-Reinhard et al, 2021; see for results)…”
Section: Studysupporting
confidence: 63%
See 2 more Smart Citations
“…Again, potential interaction effects between statistical numeracy and cultural worldview variables were extensively investigated using multiple regression analyses and other modeling and extreme group approaches. All analyses again indicated that interaction effects were consistently unreliable in accordance with Study 1 and the growing literature documenting multiple failures to replicate previously reported evidence of polarization (Ballarini & Sloman, 2017; Maguire et al, 2022; Persson et al, 2021; Shoots-Reinhard et al, 2021; see for results)…”
Section: Studysupporting
confidence: 63%
“…In contrast, there is good reason to generally expect to find the opposite. For example, the estimated unique association between numeracy and accurate climate change knowledge in the present set of studies was roughly 3 times larger than the estimated magnitude of the unreplicated polarization effect between numeracy and subjective attitudes that was observed in a small subsample of participants in prior research (Kahan et al, 2012; also see Ballarini & Sloman, 2017;Maguire et al, 2022;Persson et al, 2021;Stagnaro et al, 2023, for failure of replications; see Supplemental Material S8 for effect size comparisons). To the extent, the current findings generalize, numeracy can be expected to predict people's independent acquisition of more accurate knowledge about most risks in general, including controversial risks.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…that 5G networks were spreading the coronavirus, that injecting or ingesting bleach was a safe way to kill the coronavirus, and that the flu shot provides immunity to COVID-19 (Pickles et al, 2021). And while a recent study has shown there to be little correlation between political affiliation and interpretation of COVID-19 data, suggesting a lack of politically motivated reasoning in areas pertaining to health, it nonetheless found that individuals' attitudes towards COVID-19 were influenced by their prior beliefs (Maguire et al, 2022). There are both positives and negatives to these findings.…”
Section: In Healthmentioning
confidence: 95%
“…Beyond this conceptual issue, the replicability and generalizability of the key finding itself are unclear. While one independent team replicated the finding in an Australian sample ( 5 ), numerous others have failed to replicate it ( 6 11 ), and still others have found mixed results ( 12 14 ). Thus, the robustness of this central piece of evidence for MS2R is unclear.…”
mentioning
confidence: 94%